Phase evolution and microstructural development in sol-gel derived MSnO3 (M = Ca, Sr and Ba) - Azad, A.-M.; Hashim, M.; Baptist, S.; Badri, A.; Haq, A. Ul. (Springer, 2000)
Alkaline-earth stannates having the general chemical formula MSnO3 (M = Ca, Sr and Ba) have been projected as potential electronic ceramics. In view of the information gaps in the reported research, a vigorous and systematic investigation on these exotic materials has been carried out. In this communication, the synthesis of CaSnO3, SrSnO3 and BaSnO3 via sol-gel technique is reported. Infrared spectroscopy and X-ray analyses of various gel samples with different thermal history helped in identifying the reaction pathways and the stage where amorphous gel to crystalline phase transition occurred. Grains of submicron size with narrow size distribution and spherical morphology, were the most noticeable characteristics of sintered calcium metastannate derived by sol-gel method. In the case of barium analogue, a fascinating `sugar cube' structure (akin to that observed in solid-state reaction and the self-heat-sustained reaction derived samples) having improved density characteristics evolved at low sintering temperatures. This gradually transformed into a more familiar spherical granular motif with improved density characteristics as the sintering profiles were varied from 1200 °C/24 h to 1500 °C/2 h. This seems to be an inherent feature of this system, irrespective of the method of synthesis.